At-Risk-of-Poverty Threshold - Táňa Dvornáková (Statistika: Statistics and Economy Journal, 2012)
European Statistics on Income and Living Conditions (EU-SILC) is a survey on households’ living conditions. The main aim of the survey is to get long-term comparable data on social and economic situation of households. Data collected in the survey are used mainly in connection with the evaluation of income poverty and determinationof at-risk-of-poverty rate. This article deals with the calculation of the at risk-of-poverty threshold based on data from EU-SILC 2009. The main task is to compare two approaches to the computation of at riskof-poverty threshold. The first approach is based on the calculation of the threshold for each country separately,while the second one is based on the calculation of the threshold for all states together. The introduction summarizes common attributes in the calculation of the at-risk-of-poverty threshold, such as disposable household income, equivalised household income. Further, different approaches to both calculations are introduced andadvantages and disadvantages of these approaches are stated. Finally, the at-risk-of-poverty rate calculation is described and comparison of the at-risk-of-poverty rates based on these two different approaches is made.